PERLAWANAN PEDAGANG KAKI LIMA TERHADAP KEBIJAKAN RELOKASI PEMERINTAH DAERAH - Prasetya, Agus; Komara, Beni Dwi (Jurnal Riset Entrepreneurship, 2019)
This research was motivated by the fact that there was resistance from street vendors in Madiun City as a manifestation of people's resistance to the country. The city of Madiun, the capital city of Bakorwil 1, Madiun, is economically developing so that the number of street vendors explodes. Therefore this area is economically meaningful and has high economic value, so it becomes the goal of workers seeking, namely as street vendors. To organize the traders in the city of Madiun and the DPRD make a PKL Regional Regulation. The PKL Regional Regulation is intended to regulate the PKL selling in the city of Madiun. But the process that happened to street vendors was less involved, causing resistance. There was people's resistance to the state, because the state did not prosper the people. The regulation made by the DPRD and the Madiun city administration aims to keep traders in order, and implement the rules, but the regulation creates resistance. This study aims to: (1) understand the causes of the street vendors 'resistance (2) understand the meaning and purpose of street vendors' resistance to the Satpol PP. (3) understand the forms of street vendors' resistance to the Madiun city administration. The approach used in this study is qualitative with data collection techniques with observation, interviews and documentation. The paradigm in this study uses a social definition. While the theory used to explain the resistance of street vendors to the policies of the city government of Madiun James C. Scott's resistance theory.